P-41 Doctor´s advice for writing advanced directive and health care proxy – a written survey among family doctors in north rhine westphalia. (1st September 2015) - Schnakenberg, R; Weltermann, B; Becka, D; Althaus, A; Frank, F; Sönnichsen, A; Wilm, S; Jendik, R; Mauer, D; Bleckwenn, M
Abstract : Background: Since 2009 a new law obliges German doctors to treat their patients by their alleged will. As a result we observe an increasing demand of patient's provisions. Beside notaries, general practitioners are the preferred contact person to compose this important document. To date this advisory service is not being paid by the statutory health insurance. Therefor no reliable data are available concerning doctor's advice for writing an advanced directive or health care proxy. Aim: The questionnaire measures frequency, length and occasion of doctor's advice to write a proxy. Methods: 800 general practitioners in North Rhine-Westphalia will be surveyed with a two-sided questionnaire. The frequency of this doctor's advice will be measured by means of a five-step-scale from "five times per annum" to " > 20 times per annum". Duration of a counselling interview will be recorded in minutes. It will be differentiated between consultations that were initiated by doctor and those which were initiated by the patient. The questionnaires will be digitalized and anonymously evaluated in SPSS. There will be a pretest with general practitioners before the finalised questionnaires will be sent out. Results: The outcome will be available in summer 2015. They will give an insight into the important topic of patient's provisions and how they are composed in the setting of a GP's office. Discussion: The results will be discussed with regard to the current literature. Conclusion: The survey is meant to be a foundation for the improvement of patients' support to compose their individual health care proxy.